Study on competency of Assistant Agriculture Officers in Muda Agriculture Development Authority (MADA) - Mohammad Zakaria, Mohamad Syazwan (2016)
Rice is one of the main cultivar and the most important staple food in Malaysia. In Malaysia our production per hectare is still low which is 3.5 ton per hectare. Malaysia rice yield is about 2.4 million ton per year and only fulfill 72% of self-sufficiency level. Therefore, government give more emphasize in increasing of the rice production trough. The Malaysia Plan which is National Key Economic. It shows that the government concern about the importance of agriculture sector to feed all the people in the country. This study conducted to examine the competency of Muda Agricultural Development Authority (MADA) officers which is focus on Assistant Agriculture Officers (AAOs) as the respondents. MADA officer’s competency level can be seen through the productivity of paddy yield of farmers in Muda area. The objectives of this study are to measure the competency level and its importance among MADA officers and its relationship with the respondent’s demographic profile. There are seven (7) dimension of competency in extension activities which is planning, implementing, evaluating, communication, guiding, farm management and ICT aspect. All these type of competency will be compare with two demographic factors of respondents which is gender and years of working experience in MADA to find whether there is a significance difference between respondents demographic profile within the seven dimension of competency. The questionnaires was designed and distributed to the 163 respondents. The respondents are selected from MADA agency officers which is Agriculture Assistant Officers (AAOs). The questionnaire important to collect the information about the respondents based on their demographic profile, experience, expertise, ability and their position in MADA agency. The data will be analyzed by using Statistical Package for Social Science (SPSS) version 21.0 software for the descriptive and ANOVA. For descriptive analysis results of seven (7) dimension based on respondents competency and its importance shows the ranking ICT in extension activities (4.13) and (4.54) in the first and follows by communication (3.94) and (4.46). Guiding (3.74) and (4.36) is third and then implementing (3.74) and (4.35), planning (3.74) and (4.32) and evaluating (3.72) and (4.29). The last one is farm management in extension activities (3.53) and (4.28). For ANOVA analysis shows there are only planning and evaluating dimension of competency has a significance difference with gender of respondents while the rest is not significance. For years of working experience in MADA organization, the result indicates all of seven dimensions are not significance. The conclusion of the study shows that, there is not significance difference between seven dimensions of competency with years of working experience in MADA, the training program of MADA organization still needed to maintain the high competency level among extension agents. The results only show the majority of the respondents but not to every single of them. However, there are some extension agents has moderate and low level of competency whether their experience is high or less. This study has some limitation such as cost and time to complete. Other limitations of study are the weakness of questionnaire and also the different in understanding of the question among respondents. The recommendation and suggestion for the future study, the researcher believe that some of aspects can be improve such as questionnaire design which is qualitative or quantitative. The respondent’s age and years of working experience among them are too closed. The scope of the study can be wider and not only focus on paddy crop but also to other crops.